Piloting Self-Help Groups for Alcohol Use Disorders in Saint Vincent/Grenadines - Antonia Chen; Ynolde Smart; Amrie Morris-Patterson; Craig L. Katz (Ubiquity Press, 2014)
Background: Although alcohol consumption is recognized as a global problem, little research to date explores treatment options for alcohol use disorders in developing nations. Given the scarce mental health resources available in Saint Vincent and the Grenadines, community self-help programming for alcohol use disorders could potentially provide an important complement to the existing mental health services. Objective: The aim of this study was to gather baseline data on knowledge and attitudes toward alcohol consumption among community members, and subsequently, to pilot self-help rehabilitation programs for alcohol use disorders, while determining factors that affect the feasibility and sustainability of such programs. Methods: Focus groups were conducted in 3 communities to discuss community perceptions of alcohol use and the feasibility of self-help programs. Focus group findings guided the development and implementation of the self-help groups. A postintervention focus group was held to determine the effectiveness and community-wide effect of the self-help programs. Findings: Focus group participants agreed that alcohol consumption was a problem in Saint Vincent, leading to underage drinking and violence. Suggestions to encourage self-help meeting attendance included organizing group activities and providing visuals to illustrate alcohol's effects on health. Self-help group members were surveyed about their group experience. Of the 35 members surveyed, 77% said the group was very helpful, and 91% indicated that they would attend again. Postintervention focus group participants stated that individuals had reduced alcohol consumption after attending at least 1 self-help meeting. Conclusions: Elements that contributed to the sustainability of self-help groups included strong local leadership from district health nurses as well as willingness of participants to seek support. However, efforts need to be made to increase community awareness of alcohol use disorders and its associated dangers. Our results suggested self-help programs to address alcohol use disorders are a feasible intervention in Saint Vincent that warrants further development, dissemination, and exploration.